Clinical course after parathyroidectomy in adults with end-stage renal disease on maintenance dialysis - Lim, Christopher Thiam Seong; Kalaiselvam, Thevandra; Kitan, Normayah; Goh, Bak Leong (Oxford University Press, 2018)
Background: Parathyroidectomy (PTX) is done in cases of secondary hyperparathyroidism from chronic kidney disease to improve renal osteodystrophy. Despite this widespread practice, clinical outcomes regarding the benefits of this procedure are still lacking. Most studies in the literature have opted to report the laboratory outcome instead. Our study aimed to evaluate the postoperative clinical course for patients who had undergone total PTX without autoimplantation. Methods and results: All patients who underwent PTX between January 2010 and February 2014 in a tertiary referral center were included in this study and followed up for 12 months. Laboratory outcome parameters include various preoperative and postoperative serial measurements of laboratory parameters. Patients’ hospitalizations and mortality records post-PTX were also retrieved and recorded. In all, 90 patients were included in this study. The mean age was 48 ± 18 years. The majority of the patients (54.4%) were male and 90% were on hemodialysis. The mean duration of dialysis was 8.0 ± 5.0 years. Indications for PTX were symptomatic bone pain (95.6%), fractures (3.3%) and calciphylaxis (1.1%). Mean preoperative values for serum calcium, phosphate, alkaline phosphatase and intact parathyroid hormone (iPTH) were 2.40 ± 0.23mmol/L, 1.92 ± 0.51 mmol/L, 689.60 ± 708.50 U/L and 311.90 ± 171.94 pmol/L, respectively. The majority (92.2%) had all four glands removed and 92.2% of the glands showed hyperplasic changes. One year after PTX, 90 patients (100%) had serum iPTH <8 pmol/L and 28 patients (31%) had unmeasurable iPTH levels. A total of 15% of patients had hospitalizations for various reasons and of these, 50% were within 90 days. The mean hospital stay was 14.4 ± 18.6 days. The mortality rate was 4.4% and of these, 25% were in first 30 days. Causes of death were mainly from sepsis (75%) and acute coronary syndrome (25%). One patient (1.1%) had a relapse. Conclusions: Even though PTX markedly reduces postoperative serum iPTH levels, it carries with it significant risk of morbidity and mortality.